Offerings to the gods in Egyptian temples - Cauville, Sylvie (Peeters, 2012)
Kings and gods adorn the walls of Egyptian temples in face -to-face meetings, and for two millennia these depictions have united the king and the divine. The king, the son of the god, presents his ancestors an offering or performs a ritual. Over two hundred offerings are divided into broad categories : purification, beverages, foods, produce from the fields, fabrics, ointments and adornments ; rituals for goddesses and gods; symbolic, cosmic, funerary and defensive rituals ; and royal cult rituals. All are explained, from their simple action (e.g. offering beer as a daily drink) to their symbolic meaning (beer is also a sacred drink that induces ecstasy of a divine nature which annihilates the destructive force of the daughter of Ra). A drawing and photographs illustrate each offering. The title of the offering is given in hieroglyphs to enable everyone to locate the words on the temple walls. Translations of the most significant texts accompany each of the offerings.